Aboriginal medicinal plants of Queensland: ethnopharmacological uses, species diversity, and biodiscovery pathways - Gerry Turpin; Edita Ritmejerytė; Joanne Jamie; Darren Crayn; Phurpa Wangchuk (BMC, 2022)
Abstract Background Aboriginal peoples have occupied the island continent of Australia for millennia. Over 500 different clan groups or nations with distinctive cultures, beliefs, and languages have learnt to live sustainably and harmoniously with nature. They have developed an intimate and profound relationship with the environment, and their use of native plants in food and medicine is largely determined by the environment they lived in. Over 1511 plant species have been recorded as having been used medicinally in Australia. Most of these medicinal plants were recorded from the Aboriginal communities in Northern Territory, New South Wales, South Australia, and Western Australia. Not much has yet been reported on Aboriginal medicinal plants of Queensland. Therefore, the main aim of this review is to collect the literature on the medicinal plants used by Aboriginal peoples of Queensland and critically assess their ethnopharmacological uses. Methods The information used in this review was collected from archival material and uploaded into the Tropical Indigenous Ethnobotany Centre (TIEC) database. Archival material included botanist's journals/books and old hard copy books. Scientific names of the medicinal plant species were matched against the 'World Flora Online Plant List', and 'Australian Plant Census' for currently accepted species names to avoid repetition. An oral traditional medical knowledge obtained through interviewing traditional knowledge holders (entered in the TIEC database) has not been captured in this review to protect their knowledge. Results This review identified 135 species of Queensland Aboriginal medicinal plants, which belong to 103 genera from 53 families, with Myrtaceae being the highest represented plant family. While trees represented the biggest habit, leaves were the most commonly used plant parts. Of 62 different diseases treated by the medicinal plants, highest number of plants are used for treating skin sores and infections. Few plants identified through this review can be found in other tropical countries but many of these medicinal plants are native to Australia. Many of these medicinal plants are also used as bush food by Aboriginal peoples. Conclusion Through extensive literature review, we found that 135 medicinal plants native to Queensland are used for treating 62 different diseases, especially skin infections. Since these medicinal plants are also used as bush food and are rarely studied using the Western scientific protocols, there is a huge potential for bioprospecting and bush food industry.